Genesis of subglacial triangular-shaped landforms (murtoos) formed by the Fennoscandian Ice Sheet - Mäkinen Joni; Kajuutti Kari; Ojala Antti EK; Ahokangas Elina; Tuunainen Aleksi; Valkama Markus; Palmu Jukka-Pekka (WILEY, 2025)
The purpose of this paper is to describe the internal structure and composition of recently discovered subglacial landforms called "murtoos" in order to interpret their formative processes and depositional environment. So far, murtoos have only been reported from Finland and Sweden, but they probably exist in all areas covered by past ice sheets. Murtoos mainly occur in fields along subglacial meltwater routes or corridors in close relation to eskers and ribbed moraine tracts. Murtoos were excavated perpendicular to the long axes of the triangular murtoo heads in six locations. Murtoos were found to be composed of silt/clay-poor, sandy and gravelly diamictons interbedded with sorted sediments, and are suggested to be produced by pulsed, highly sediment-concentrated flows during weak glaciotectonic deformation, indicating effective pressure close to zero. Murtoos can be divided into three main depositional units: 1) the core, 2) the murtoo body and 3) the murtoo mantle. The initial deposition of murtoos took place in a network of low canals and conduits or cavities with fluctuating stream flow likely over 50 km from the ice margin. Murtoos reveal an increasing influence of subglacial meltwater flow in rapidly widening broad and low conduits with increasing sediment transport over short distances. The results of this work suggest that murtoos were formed time-transgressively over yearly meltwater cycles in a semi-distributed drainage system not recognised before, in which was high-pressure porewater conditions with rapid mobilisation of subglacial saturated sediments, a critical factor in the development of semi-efficient drainage. Murtoos are suggested as missing element between distributed and channelised drainage systems not included in current glaciohydrological models or even in the theoretical basis of glacial hydrology.